Self-reported Improvement in Side Effects and Quality of Life With Integrative Medicine in Breast Cancer Patients. (September 2018) - Hack, Carolin C.; Hackl, Janina; Hüttner, Nina B. M.; Langemann, Hanna; Schwitulla, Judith; Dietzel-Drentwett, Svenja; Fasching, Peter A.; Beckmann, Matthias W.; Theuser, Anna-Katharin
Purpose. Although the demand from patients for integrative medicine is increasing, complementary medicine services are still quite heterogeneous and have not been incorporated into clinical routine. The aim of this study was to systematically evaluate improvements in side effects and quality of life associated with a hospital-based integrative medicine program in the modern breast cancer patient care setting. Methods. In a cross-sectional study, integrative health counseling and treatment were evaluated in women with breast cancer. Over a 15-month period, data for 75 patients from an integrative medicine consultancy service with standardized operating procedures were collected at the University Breast Center for Franconia. At baseline, the patients answered a questionnaire on their medical history, symptoms, and the treatment goals they were hoping to achieve with integrative medicine. In the follow-up, patient-reported outcomes related to side effects of conventional cancer treatment and patients' quality of life were analyzed. Results. Among 60 patients with the therapy goal of reducing the side effects of conventional treatment, 46 (76.7%) were successful. Among 57 patients hoping to improve disease-related quality of life, 46 (82%) reported success. Whereas patients with metastatic disease achieved a reduction in the side effects of conventional therapy, quality-of-life improvements were predominantly achieved by patients with a good treatment prognosis. Conclusions. Breast cancer patients benefit from the counseling and treatment provided with integrative medicine in all phases of tumor disease. Integrative treatment services should be included as part of patient care in clinical routine work to offer patients the maximum quality of care and safety with complementary therapies.